Evaluation of Percutaneous Absorption of Esculetin: Effect of Chemical Enhancers - del Rio Sancho, Sergio; Serna Jiménez, César Eulogio; Calatayud Pascual, María Aracely; Balaguer Fernández, Cristina; Femenía Font, Andrés; Castillo García, Encarna; Merino, Virginia; López Castellano, Alicia (Planta Medica, 2013)
Percutaneous transdermal absorption of esculetin (6,7-dihydroxycoumarin), an oxidative damage inhibitor, was evaluated by means of in vitro permeation studies in which vertical Franz-type diffusion cells and pig ear skin were employed. To determine the absorption of esculetin, we validated a simple, accurate, precise, and rapid HPLC-UV method. Additionally, the effects of several percutaneous enhancers were studied. Pretreatment of porcine skin was performed with ethanol (control vehicle), decenoic acid, oleic acid, R-(+)-limonene, and laurocapram (Azone®) (5 % in ethanol, w/w, respectively). Pretreatment of skin with oleic acid or laurocapram led to statistically significant differences in the transdermal flux of esculetin with respect to controls. Of the two enhancers, laurocapram showed the greatest capacity to enhance the flux of esculetin across pig skin.
Keywords: esculetin; absorption enhancer; in vitro model; transdermal drug delivery